Design of a Propotional Resonant Controller with a Fractional Order PID for Improving Voltage Regulation in a Multi-Bus Microgrid System (International Journal of Food and Nutritional Sciences, 2021)
Due to the shadow impact on solar PV systems, unpredictable variations in wind turbine speed, and single-phase loads, improving dynamic responsiveness and voltage control in multi-Bus Microgrid systems is a hard task. In order to improve dynamic responsiveness and voltage regulation in a multi-bus microgrid system, this study describes the design of fractional order PID (FOPID) and proportional resonant controllers (PR). The Quadratic Boost Converter (QBC) modelling analysis is used to increase the output voltage of solar PV systems. The proper switching pulses (or signals) for the QBC are created by the closed loop FOPID & PR controllers. By varying the duty cycle of the QBC, these switching pulses will affect the multi-bus microgrid system's dynamic responsiveness and voltage regulation is enhanced. In the MATLAB/Simulink environment, the comparison of dynamic behaviour and time domain load voltage characteristics at bus-3 utilising FOPID and PR controllers is examined